Digital Sovereignty in International Relations: The Contest for Data Control in Global Politics - Aan Herdiana (Synergisia, 2026)
Digital sovereignty has emerged as one of the most contested issues in contemporary international relations, reflecting a new geopolitical competition centered on the control of data, technological infrastructure, and cyberspace. This article examines the concept of digital sovereignty through the lens of international relations theory, analyzing how major actors, particularly the United States, the European Union, China, and emerging economies, construct and contest claims of digital sovereignty in the global arena. Through a systematic review of 20 peer-reviewed journal articles (2021–2024), this study identifies three principal dimensions: (1) normative contestation in the definition of digital sovereignty; (2) data regulation as an instrument of geopolitical power; and (3) internet fragmentation (splinternet) as a consequence of competing sovereignty claims. The findings demonstrate that digital sovereignty is not merely policy rhetoric but a genuine arena of contestation between national security interests, corporate technological dominance, and citizens' digital rights.